2021
DOI: 10.1088/1748-9326/abf9c8
|View full text |Cite
|
Sign up to set email alerts
|

Acting rapidly to deploy readily available methane mitigation measures by sector can immediately slow global warming

Abstract: Methane mitigation is essential for addressing climate change, but the value of rapidly implementing available mitigation measures is not well understood. In this paper, we analyze the climate benefits of fast action to reduce methane emissions as compared to slower and delayed mitigation timelines. We find that the scale up and deployment of greatly underutilized but available mitigation measures will have significant near-term temperature benefits beyond that from slow or delayed action. Overall, strategies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
123
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 190 publications
(128 citation statements)
references
References 35 publications
2
123
0
3
Order By: Relevance
“…Further, the aggregation of GHG emissions, using GWP100 as required by the UNFCCC, makes it difficult to unambiguously determine the climate impact of the Paris Agreement emission goal of “peaking of GHG emissions as soon as possible” and undertaking “rapid reductions thereafter” 11 , because the breakdown between short- and long-lived GHG emissions is unknown; for example one could increase short-lived GHG emissions but decrease long-lived GHG emissions, with a net decrease that suggests a peak and decline, but more warming in the following few decades. Given that effective strategies exist to reduce near-term climate damages 25 , 26 , it is important that climate policies pursue these actions as well as those focused on stabilizing the climate. Together, cumulative damages can be reduced relative to those incurred from focusing on only one of these objectives.…”
Section: Common Misconceptions Of Net Zero Targetsmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, the aggregation of GHG emissions, using GWP100 as required by the UNFCCC, makes it difficult to unambiguously determine the climate impact of the Paris Agreement emission goal of “peaking of GHG emissions as soon as possible” and undertaking “rapid reductions thereafter” 11 , because the breakdown between short- and long-lived GHG emissions is unknown; for example one could increase short-lived GHG emissions but decrease long-lived GHG emissions, with a net decrease that suggests a peak and decline, but more warming in the following few decades. Given that effective strategies exist to reduce near-term climate damages 25 , 26 , it is important that climate policies pursue these actions as well as those focused on stabilizing the climate. Together, cumulative damages can be reduced relative to those incurred from focusing on only one of these objectives.…”
Section: Common Misconceptions Of Net Zero Targetsmentioning
confidence: 99%
“…We focus on these two gases because they account for over 70% of today’s positive radiative forcing from GHG emissions to date, and they also represent the dominant long-lived and short-lived GHGs, respectively, for both current and future warming in the absence of climate action 42 . While the paths we consider are generally illustrative, they are within the range of emissions pathways projected by integrated assessment models 9 or considered technically achievable 25 , 26 , 46 , 47 . However, actual carbon dioxide and methane reductions over time can take many forms, and socio-economic constraints and large-scale deployment of various technologies, such as negative emissions technologies, will play a major role in determining exact paths.…”
Section: The Role Of the Net Zero Path In Determining Climate Outcomesmentioning
confidence: 99%
“…Hence, they propose the introduction, by 2050, of institutional reforms and changes to human nutritional habits on a broad scale, in addition to the implementation of technological solutions. Meanwhile, Ockoet al [54] believe that achieving a reduction of methane and nitrous oxide emissions by changing the human diet is less realistic than implementing technological strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Both of these large emission sources are under man-made control, meaning their abatement is possible and desirable in the context of GHG emission reduction plans. Both past evaluations and a more recent work [3][4][5] have shown that the associated methane emission reductions would be effective in reducing both the rate of global warming as well as the ultimate level of warming by 2100, in various scenarios of development.…”
Section: Introductionmentioning
confidence: 99%